Penggunaan Akar Tanaman Antagonis Untuk Menekan Puru Akar Oleh Nematoda (Meloidogyne spp) Pada Tanaman Tomat (Lycopersicum Esculentum Miller.) - Rifai, Eby H; Uluputty, Muhammad R; Umasangadji, Aminudin (Tropical Small Island Agriculture Management, 2024)
This research aims to determine the effect of antagonistic plant roots in suppressing the formation of root knots by nematodes on tomato plants. This research used a Completely Randomized Design (CRD) consisting of 5 treatments and 5 replications. This research was carried out in Negeri Rumah Tiga, Teluk Ambon District. The research results showed that castor root extract (Recinus communis Linn.) was better than areca root extract (Areca catchu Linn.) and papaya root extract (Carica Papaya Linn.) in suppressing the growth of root knot nematodes on tomato plants (Lycopersicum esculentum Miller. ). Secondary metabolism contained in castor root extract (Recinus communis Linn.) has an effect in suppressing root length growth by 24.46 cm, while the substances contained in papaya root extract (Carica papaya Linn) suppress root length growth by 14.34 cm. The root weight of the tomato plant, Moringa oleifera Linn.) root extract weighed 0.8 grams, while the lowest was the kenikir (Cosmos caudatus Linn.) root extract with a root weight of 0.23 grams. Castor root extract (Recinus communis Linn.) from areca root extract (Areca catchu Linn.) and papaya root extract (Carica papaya Linn.) in suppressing the growth of root knot nematodes on tomato plants (Lycopersicum esculentum Miller.). The damage value of areca root extract (Areca catchu Linn.) and papaya root extract (Carica papaya Linn.) have the same high damage value, namely 2.2, while castor root extract (Recinus communis Linn.) has a low damage value of 1.2.